Mixed Manufacturer Combination With a Cementless Hemispherical Dual Mobility Cup and Polished Taper-Slip Cemented Femoral Stem: Short- to Medium-Term Results in Primary Total Hip Arthroplasty in Elderly Patients - Blaise Pellegrini, MD; Alexander Antoniadis, MD; Diane Wernly, MD; Maya Kaegi, MD; Julien Wegrzyn, PhD (Arthroplasty Today, 2025)
Background: There is a lack of conclusive literature regarding the mixed-manufacturer combination of the Symbol cementless hemispherical dual mobility cup (Dedienne Santé) and the Exeter V40 cemented femoral stems (Stryker) in patients who underwent primary total hip arthroplasty (THA). This study aimed to evaluate the clinical and radiographic outcomes of this combination, with a particular attention to the occurrence of dislocation and periprosthetic femoral fractures (PFFs). Methods: Between 2021 and 2023, a consecutive series of 123 primary THAs were reviewed at the latest follow-up. The mean age at surgery was 75 ± 9 ys. Postoperative complications were recorded. The clinical outcome was assessed with the Harris Hip Score. Acetabular, femoral, and global hip offset were evaluated on standard radiographs. Results: At a mean follow-up of 23 ± 7 months, the mean preoperative to postoperative Harris Hip Score improved significantly from 46 to 93 (P < .0001.) No dislocation was reported. No Vancouver A or B PFF was observed. One Vancouver C PFF was observed. The revision-free survival rate at 24-month follow-up was 98.6%. The global offset of the hip was restored in all the patients with a mean average increase of 3 ± 5.8 mm. Conclusions: The mixed-manufacturer combination of the Symbol cementless hemispherical dual mobility cup and the Exeter cemented femoral stem resulted in excellent short- to medium-term outcomes in patients who underwent primary THA. This combination was effective in preventing both instability and femoral Vancouver B PFF in these patients at risk, while allowing global hip offset restoration.